Study guides

☆☆

Q: What is 2x2 plus 3x plus 1?

Write your answer...

Submit

Still have questions?

Related questions

2x2 + 3x + 1 = (x + 1)(2x + 1)

If: 2x2-3x+1 = 0 Then: x = 1 or x = 1/2

No.

d/dx 2x2+3x+7=4x+3

2x2 equals 5

No. You'd have to use the ABC-formula

This expression could be reordered as 1 + 3x + 2x2.

The discriminant is 1.

-11

(x-1)(2x+5)

(3x - 1)(2x2 - 2x - 1)

x3 + 2x2 - 3x - 6 = (x2 - 3)(x + 2)

(2x - 1)(x - 1) so x = ½ or 1

factorises as (2x + 1)(x + 1) so x = -0.5 or -1

2x2 + 3x - 20 = (x + 4)(2x - 5).

2x2-3x-5 = (2x-5)(x+1) when factored

3x3=9 -2x2=-4 so, 9-4=5 7x4=28 so, 28+5=33 33+3x-1=0 -1 32+3x=0 -32 -32 3x=-32 x=-32/3 or -10 2/3 or 10.67

2x2-4x-3x+6 2x2-7x+6 (2x+3)(x+2)

(2x + 7)(x - 2)

(x + 1) / (2x3 + 3x + 5) --- Can't depict long division here, but you can work this out by seeing if (x + 1) is a factor of (2x3 + 3x + 5). If it is, then the answer will be 1/(the other factor). In this case, that is true. (2x3 + 3x + 5)/(x + 1) = 2x2 - 2x + 5, so the term term above is equal to: 1 / (2x2 - 2x + 5)

(x4 - 2x3 + 2x2 + x + 4) / (x2 + x + 1)You can work this out using long division:x2 - 3x + 4___________________________x2 + x + 1 ) x4 - 2x3 + 2x2 + x + 4x4 + x3 + x2-3x3 + x2 + x-3x3 - 3x2 - 3x4x2 + 4x + 44x2 + 4x + 40Râˆ´ x4 - 2x3 + 2x2 + x + 4 = (x2 + x + 1)(x2 - 3x + 4)

(x-2)(2x+7)

65

If you mean: 2xsquared+3x+1 then it is (2x+1)(x+1) when factored

y = 2x2 - 3x + 1 y = (x - 1)(2x - 1) x - 1 = 0 2x - 1 = 0 x = 1 x = 1/2 the answer is 2